Penerapan Lembaga Constitutional Importance Pada Komisi Nasional Hak Asasi Manusia - Aprilio, Dhuha; Khairul Fahmi; Charles Simabura (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2025)
Implementation of the concept of constitutional interest institutions in the National Human Rights Commission (Komnas HAM) in Indonesia. This is the response of independent state institutions in response to public confidence in the global trade and Commerce watchdog on human rights issues. The purpose of the study was to analyze the relationship of Komnas HAM as an institution of constitutional interest in the Indonesian Constitutional system. The method used is normative juridical research with data collection techniques through literature studies. Development involves the concept of independent state institutions, guidelines for the development of these institutions, as well as regulations and guidelines of Komnas HAM as an institution that has constitutional importance. The results showed that Komnas HAM has an equal position with other state institutions and plays a role in maintaining the balance of power and protecting human rights in accordance with constitutional principles. This investigation concluded that the authority of Komnas HAM as an institution of constitutional importance affects Indonesia's commitment to human rights protection and helps enforce checks and balances in the constitutional system.